The Influence of Work Motivation on Employee Work Performance at the Bima City Tourism and Culture Office - Miswarita, Eka; Mulyadin, Mulyadin; Jaenab, Jaenab (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
. This research aims to determine the effect of work motivation on employee work performance at the Bima City Tourism and Culture Office. This research is included in the Associative research category. The research instrument used was a questionnaire with a Likert scale. The population used in this research was all employees at the Bima City Tourism and Culture Office, totaling 58 employees, consisting of 34 employees with civil servant status and 18 contract employees and 6 honorary employees. The sample in this study was 34 employees with civil servant status at the Bima City Tourism and Culture Office. The sampling technique used in this research is purposive sampling technique. Data collection techniques use observation, questionnaires and literature study. The data that has been collected is then analyzed using SPSS v.26 then tested for validity, reliability test, simple linear regression analysis, correlation coefficient, determination test and t test. The research results show that there is a significant influence of work motivation on work performance at the Bima City Tourism and Culture Office.